Crossed categorization in common ingroup contexts. - Crisp, R; Walsh, J; Hewstone, M (2006)
In three experiments, the authors tested the hypothesis that a common ingroup context would moderate evaluations of crossed category targets. In Experiment 1, the typical additive pattern of evaluation across artificial crossed category groups became a social inclusion pattern in a common ingroup context. In Experiment 2, the authors manipulated the importance of real crossed category targets. When the crossed groups were of low importance, the effects of imposing a common ingroup replicated those observed in Experiment 1. For important crossed groups, however, the additive pattern remained. In Experiment 3, the authors measured perceived importance of the crossed groups to social identity prior to introducing a common ingroup context. The effects of a common categorization on evaluations were again moderated by perceived importance. These findings are discussed in the context of integrating crossed categorization and common ingroup identity models of multiple categorization.